PERANAN AUDIT INTERNAL TERHADAP KINERJA PERUSAHAAN PT. PERKEBUNAN NUSANTARA III KEBUN RAMBUTAN - Maya Sartika Sinaga; Ratna Dina Marviana (UNIVERSITAS DHARMAWANGSA, 2022)
Internal auditors have an important role in a company, because the role of internal auditors has an effect on increasing company performance. The formulation of the problem in this study is how the role of internal audit on the company's performance at PT. Nusantara III Plantation Rambutan Plantation. The purpose of this study was to determine the role of internal audit on company performance at PT. Nusantara III Plantation Rambutan Plantation.The type of data in this study is qualitative data in the form of documents, explanations, and information. This study uses primary and secondary data sources. Primary data is in the form of interviews with the System and Certification Document Officer (DSS) and observation activities which will then be processed by the author, secondary data for example company organizational structure, company audit reports, company history. The data collection technique in this study is to conduct field research, namely visiting directly to the research site and by conducting library research, namely by reading sources such as books or literature related to research. The data analysis method used is the Descriptive Analysis Method. From the results of this study it can be concluded that the Role of Internal Audit on Company Performance at PT. Perkebunan Nusantara III Kebun Rambutan is to examine and assess efficiency and effectiveness in finance, operations, human resources, information technology with the aim of strengthening the governance system. To ensure the reliability of information, the implementation of internal audit is also in accordance with company standards, where the internal audit function is to provide follow-up advice to achieve company goals efficiently, effectively on audit findings.